Denmark : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper describes economic developments in Denmark during 1990-96. After a prolonged period of stagnation in the second half of the 1980s and early 1990s, GDP rose by 4u percent in 1994, reflecting a surge in domestic demand and recovery in export markets. The expansion of GDP slowed to a 2 3/4 percent pace in 1995 as domestic demand moderated and as exports decelerated sharply. The slowing of external markets intensified in the course of 1995 with the result that GDP in the fourth quarter was barely above its first quarter level.